Description on Scientific Research and Method - Sergio Baragetti (Current Approaches in Science and Technology Research Vol. 10, 2021)
This chapter reports a short critical and historical analysis of the scientific method. Concepts coming from the XVII Century will be considered and discussion will proceed through the Centuries until today. The question is: what did change since the XVII Century in scientific research?